An audit approach of the information systems auditor in an electronic commerce environment with emphasis on internet payment security - Gloeck, Juergen D. (Juergen Dieter), 1956- (University of Pretoria, 2013)
Dissertation (MCom (Computer Auditing))--University of Pretoria, 2006.